Rising concentration and wage inequality - Guido Matias Cortes; Jeanne Tschopp (University of Bern, Department of Economics, 2020)
Wage inequality has risen in many countries over recent decades. At the same time, production has become increasingly concentrated in "superstar" firms. In this paper, we show that these two phenomena are linked. Theoretically, we show that shocks that increase concentration, such as an increase in consumers' price sensitivity, will also lead to an increase in wage dispersion between firms. Empirically, we use industry-level data from 14 European countries over the period 1999-2016 and show robust evidence of a positive and statistically significant correlation between concentration and the dispersion of firm-level wages.
Keywords: 330; Lohnstruktur; Produktion; Unternehmenskonzentration; Schock; EU-Staaten